Development of milk powder reference material and its use for evaluation of laboratory performance on analysis of mandatory nutrients for nutrition labelling in Thailand - Kunchit Judprasong (2018)
© 2017, Springer-Verlag Berlin Heidelberg. This study investigated the laboratory performance on the analyses of mandatory nutrients for nutrition labelling in Thailand and aimed to upgrade the proficiency test (PT) material into a reference material (RM). This milk powder with sufficient homogeneity and multiple nutrient compositions provided an acceptable PT material. Twenty ISO 17025 accredited laboratories participated in this study, and analytical performance was investigated using ISO 17043 and ISO 13528 standards. Satisfactory performance (|z| ≤ 2, for both within- and between-laboratory variations) was found among participating laboratories on the analyses of total fat, saturated fat, cholesterol, protein, sugar, sodium, vitamin B1, vitamin B2, calcium, iron, moisture, and ash. The values of these nutrients (mean and standard deviation) were applied to upgrade the PT material to be used as a reference material. For a trial, moisture, vitamin B1, and vitamin B2were selected as three representative nutrients to develop reference values as mean and uncertainty following ISO Guides 34 and 35 for RM production. The mean of moisture, vitamin B1, and vitamin B2values of 2.34 g/(100 g), 0.64 mg/(100 g), and 0.78 mg/(100 g) were obtained with the relative expanded uncertainty of 12.2 %, 12.7 %, and 9.7 %, respectively. The developed RM can be used as quality control sample or as PT material with reference nutrient values among the laboratories in Thailand.